1977
DOI: 10.1055/s-0028-1097519
|View full text |Cite
|
Sign up to set email alerts
|

CONSTITUENTS OFHOLOPTELEA INTEGRIFOLIAHEARTWOOD

Abstract: The bark yields ,6-sitosterol, oleanolic acid a n d hederagenin besides the triterpenoid already reported.Holoptelea integrifolia PLANCH. syn. Ulmus integrifolia ROXB. (Ulmaceae) locally known as Chilbil is the only representative of the genus found in India [I].It is a roadside tree distributed throughout the country. The bark [2] yields friedelin and friedelan-38-01 while the leaves [2] yield hexacosanol, octacosanol, ,6-sitosterol and ,9-amyrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…T h e d e e p swe e p i n t h e ava i l a bl e literature [15][16] concluded that the unsaponifiable matter under examination was identical with the known compound β-sitosterol (mmp, Co-PC, Co-TLC) (I). The identity of the compound was further confirmed by mmp.…”
Section: Resultsmentioning
confidence: 99%
“…T h e d e e p swe e p i n t h e ava i l a bl e literature [15][16] concluded that the unsaponifiable matter under examination was identical with the known compound β-sitosterol (mmp, Co-PC, Co-TLC) (I). The identity of the compound was further confirmed by mmp.…”
Section: Resultsmentioning
confidence: 99%
“…(Mughsi, Indian Elm Tree), a roadside plant is a native of Asian tropical regions including India, China, Nepal and Srilanka [12]. The plant belongs to family Ulmaceae and is well known in traditional medicine being used as anti-inflammatory [13], antioxidant, antimicrobial and anticancer agent [14,15]. Considering the potential anticancer activity of phytochemicals in the leaves and stem bark [16], we investigate the anticancer potential of methanolic extract of Holoptelea integrifolia (Roxb)Planch fruit in this study.…”
Section: Operculinamentioning
confidence: 99%